2014
DOI: 10.1155/2014/901276
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Dengue Virus Nonstructural Protein 1 Serum Levels and Altered Toll-Like Receptor 4 Expression, Nitric Oxide, and Tumor Necrosis Factor Alpha Production in Dengue Hemorrhagic Fever Patients

Abstract: Background. During dengue virus (DV) infection, monocytes produce tumor necrosis factor alpha (TNF-α) and nitric oxide (NO) which might be critical to immunopathogenesis. Since intensity of DV replication may determine clinical outcomes, it is important to know the effects of viral nonstructural protein 1 (NS1) on innate immune parameters of infected patients. The present study investigates the relationships between dengue virus nonstructural protein 1 (NS1) serum levels and innate immune response (TLR4 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Our results showed that the expression of TLR-4 was significantly upregulated on both CD14 + CD16 − and CD14 + CD16 + monocyte subsets, and on CD14 − CD16 − subsets of macrophages in ZIKV immune animals at day 63 post-ZIKV infection (day 7 post-DENV-2) as compared to day 0 and 56 post-ZIKV infection (time points prior to DENV-2 infection) suggesting that DENV-2 infection was accompanied by a significant activation of inflammatory subsets of monocyte/macrophages. Previous studies have reported that TLR-4 expressing CD14 + cells significantly increased in DENV patients 27 , 29 , and DENV directly activated human macrophages via TLR-4 leading to the induction and release of pro-inflammatory cytokines, and this effect was inhibited with TLR-4 antagonists, and anti-TLR-4 antibody 30 . Others have shown that non-classical monocytes (CD14 + CD16 + ) produce significant levels for pro-inflammatory cytokines 31 .…”
Section: Resultsmentioning
confidence: 91%
“…Our results showed that the expression of TLR-4 was significantly upregulated on both CD14 + CD16 − and CD14 + CD16 + monocyte subsets, and on CD14 − CD16 − subsets of macrophages in ZIKV immune animals at day 63 post-ZIKV infection (day 7 post-DENV-2) as compared to day 0 and 56 post-ZIKV infection (time points prior to DENV-2 infection) suggesting that DENV-2 infection was accompanied by a significant activation of inflammatory subsets of monocyte/macrophages. Previous studies have reported that TLR-4 expressing CD14 + cells significantly increased in DENV patients 27 , 29 , and DENV directly activated human macrophages via TLR-4 leading to the induction and release of pro-inflammatory cytokines, and this effect was inhibited with TLR-4 antagonists, and anti-TLR-4 antibody 30 . Others have shown that non-classical monocytes (CD14 + CD16 + ) produce significant levels for pro-inflammatory cytokines 31 .…”
Section: Resultsmentioning
confidence: 91%
“…In contrast to TNF and IL‐6, which are higher in ADE of DENV, production of NO in THP‐1 cells was significantly reduced . Lower serum NO levels were also observed in DHF patients who had higher NS1 levels during the acute febrile phase, compared with patients with mild dengue fever , suggesting that DENV can suppress NO. However, the data on NO in DENV infection are conflicting.…”
Section: Characterizing Ade Of Virus Infection: Denv As a Case Studymentioning
confidence: 86%
“…Several inflammatory cytokines, including tumor necrosis factor alpha (TNF-α), interferon-γ, and IL-6, are reported to be highly released in patients with DHF, which is a clinical characteristic of DHF3334. Although aberrant activation of COX-2 is associated with severe inflammation and viral pathogenesis, the role of COX-2 in the pathogenesis of DHF remains unclear.…”
Section: Discussionmentioning
confidence: 99%